Childhood Trauma and Neurocognition in Adults With Psychotic Disorders: A Systematic Review and Meta-analysis. (30th October 2018) - Vargas, Teresa; Lam, Phoebe H; Azis, Matilda; Osborne, K Juston; Lieberman, Amy; Mittal, Vijay A
Abstract: Background: Characterizing the link between childhood trauma and adult neurocognitive function in psychosis is crucial for improving the fields understanding of how early environmental risk factors impact the presentation of the disorder. To date, the literature has been inconsistent: meta-analytic synthesis is lacking, and it is unclear whether specific cognitive functions are affected. Methods: A meta-analysis was performed on a total of 3315 subjects with a psychotic disorder. The links between childhood trauma, overall neurocognitive function, and four cognitive subdomains (working memory, executive function, verbal/visual memory, and attention/processing speed) were examined. Relevant sample characteristics and methodological moderators were tested. The strength of the association between trauma and overall neurocognition in individuals with psychotic disorders was also compared to that of healthy controls. Results: Among individuals with psychotic disorders, there was a significant association between overall cognition and childhood trauma, r = −.055; 95% CI = −0.09, −0.02, P = .002. There was also a modest, negative relationship between childhood trauma and working memory, r = −.091; 95% CI = −0.15, −0.03, P = .002. Moderators did not have a significant effect on these analyses. Further, the association between childhood trauma and neurocognition was significantly stronger in healthy controls compared to patients with a psychotic disorder. Conclusion: A small negative association was found between overall cognition and childhood trauma in individuals with psychotic disorders. Results suggest the association is less strong for individuals with a psychotic disorder compared to healthy populations. Findings are informative for prominent etiological models of psychosis.